CELL MEMBRANE - Abdunazarov Mirzhalol Khudoyshukur ugli; Sultonov Akhrorbek Doniyorbek ugli; Yuldashov Khusniddin Eshnazarovich; Bekmirzaev Eshkuvvat Ruziboevich; Kurbonova Gulnoza Abdirakhimovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article will consider the structure, structure, components and functions of the cell membrane.